The hermit thrush - Mathews, F. Schuyler (Ferdinand Schuyler), 1854-1938 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Hermit Thrush" by F. Schuyler Mathews is a poetic work likely written in the late 19th century. It combines elements of nature writing and lyrical poetry, focusing on the beauty and sounds of the natural world, particularly the songs of the hermit thrush. This work encapsulates themes of solitude, nature's tranquility, and the emotional resonance of nature$1 (Bs music. In "The Hermit Thrush," the narrator paints a vivid picture of a hermit thrush who resides in a secluded woodland area, far from human presence. The poem describes the bird's enchanting song, which resonates throughout the peaceful landscape, capturing the essence of springtime. The thrush's melody is portrayed not just as a simple tune but as a profound expression of joy and melancholy, drawing listeners into the serene beauty of the wilderness. With references to the local geography, such as the blue hills and various natural features, Mathews invites readers to connect with the peaceful yet emotionally complex world of nature as seen through the lens of the hermit thrush's hymn. (This is an automatically generated summary.)s
Release date is 2023-02-10
Steve Mattern, Barry Abrahamsen, and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: American poetry -- 19th century; New Hampshire -- Poetry; Hermit thrush -- Poetry